Revolutionizing Online Higher Education: A Theoretical Approach - Maspul, Kurniawan Arif (Yayasan Insan Mulia Bima, 2024)
Understanding the theoretical foundations of online learning becomes increasingly important as education shifts online. This article examines the theoretical frameworks of constructivism and connectivism. The integration of these theories in the design and execution of online learning environments is examined, with a focus on student engagement, technological access, and knowledge networks. The importance of online learning in serving the different requirements of learners around the world is underlined, especially in terms of adaptation and accessibility. The COVID-19 pandemic increased the spread of online education, highlighting the significance of digital infrastructure and training. Accredited online programs, founded on solid theoretical foundations, provide high-quality education comparable to traditional degrees The advantages of online learning are underlined, including self-directed learning, digital literacy, and inclusion. The study takes a qualitative approach, combining literature analysis, interviews with educators, and personal observations to present a full examination of the quality and recognition of online degree programs. Educators may build effective online learning experiences that address the changing needs of modern learners by understanding and utilizing these theoretical frameworks.